A case-report of a pulmonary tuberculosis with lymphadenopathy mimicking a lymphoma. (May 2018) - Collu, Claudia; Fois, Alessandro; Crivelli, Paola; Tidore, Gianni; Fozza, Claudio; Sotgiu, Giovanni; Pirina, Pietro
Abstract: Clinical and radiological manifestations of tuberculosis (TB) are heterogeneous, and differential diagnosis can include both benign and malignant diseases (e.g., sarcoidosis, metastatic diseases, and lymphoma). Diagnostic dilemmas can delay appropriate therapy, favoring Mycobacterium tuberculosis transmission. We report on a case of TB in an immunocompetent, Somalian 22-year-old boy admitted in the respiratory unit of an Italian university hospital. His symptoms and clinical signs were thoracic pain, weight loss, latero-cervical, mediastinal, and abdominal lymphadenopathy. Smear microscopy and PCR were negative for Mycobacterium tuberculosis . The unclear histological pattern, the unusual clinical presentation, the CT scan signs, the BAL lymphocytes suggested the suspicion a lymphoma. Culture conversion proved Mycobacterium tuberculosis infection. This case report highlights the risk of misdiagnosis in patients with generalized lympho-adenopathy and pulmonary infiltrates, particularly in Africans young patients.